PENGARUH ENTERPRISE RISK MANAGEMENT TERHADAP KINERJA KEUANGAN PERUSAHAAN - Muhammad Faisal Anfasah Mutaz (2021)
This research is a quantitative study with the aim of knowing the effect of enterprise risk management on firm performance. This study uses non-financial state-owned companies listed on the IDX as a sample. The selection used purposive sampling after determining the number of samples that can be accepted, namely as many as 16 companies. Hypothesis testing in this study used Multiple Linear Regression Analysis with the SPSS program and a significance level of 0.05 (5%). The results of the test are (1) firm performance is not significantly affected by CRO centrality (2) firm performance is not significantly affected by risk committee training (3) firm performance is not significantly influenced by risk committee meetings (4) firm performance is not significantly affected by the frequency of assessments risk (5) firm performance is not significantly affected by the level of risk assessment (6) firm performance is not significantly affected by risk assessment methods.